Faktor-faktor yang berhubungan dengan pemberian asi eksklusif pada ibu bekerja di kecamatan gondokusuman kota yogyakarta - Yayang Windi Astuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
Indonesia has targeted the national exclusive breasfeeding coverage is 80%. Indonesia's exclusive breasfeeding coverage in 2017 is 35.7% The exclusive breasfeeding coverage of Yogyakarta is only 66.13%. Exclusive breasfeeding coverage is still low for various reasons one of them is a working mother. Research objectives: Known factors that relate to the exclusive breastfeeding knowledge, attitudes, availability of the breastfeeding facilities during work, husband support, and healthcare personnel support in the sub-district Gondokusuman. Method: This research uses cross sectional design. The population in this research is all mothers who have a baby aged 6-12 months. The sampling technique used is purposive sampling. Sample count of 47 samples. Data analysis using Chi-square test. Results: Data analysis results obtained that there is a significant relationship of knowledge (p value 0.038; CC 0.350), attitude (p value 0.007; CC 0.366), availability of a breastfeeding facility during work (p value 0.001; CC 0.425), husband support (p value 0.019; CC 0.325) and healthcare personnel support (p value 0.011; CC 0.349) with exclusive breastfeeding on working mothers. Conclusion: There is a significant relationship between knowledge, attitude, availability of the breastfeeding facility during work, husband support and healthcare personnel support with exclusive breastfeeding in the working mother.